2011
DOI: 10.3390/molecules16097377
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to New (5Z) 2-Alkylthio-5-arylmethylene-1-methyl-1,5-dihydro-4H-imidazol-4-one Derivatives

Abstract: A practical protocol for the preparation of (5Z)-2-alkylthio-5-arylmethylene-1-methyl-1,5-dihydro-4H-imidazol-4-one derivatives is reported. The new compounds were obtained in good yield and stereoselectivity in two steps, namely a solvent-free Knoevenagel condensation under microwave irradiation, followed by an S-alkylation reaction with various halogenoalkanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…[27][28][29][30] When using halogen-containing compounds (chloroacetonitrile, alkyl bromoacetates, allyl bromide, propyl bromide), the French authors have shown a low reactivity of some chloro-and bromoalkanes, that impelled them to add one equivalent of KI to the reaction mixture. [31] To the best of our knowledge, prior to the present study, there had been no report on the alkylation of thiohydantoin or its derivatives with α-iodoketones that might lead to the corresponding salts. The need for the salts of heterocyclic compounds is determined by the growing interest in these compounds due to wide application in different fields of science and technology.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…[27][28][29][30] When using halogen-containing compounds (chloroacetonitrile, alkyl bromoacetates, allyl bromide, propyl bromide), the French authors have shown a low reactivity of some chloro-and bromoalkanes, that impelled them to add one equivalent of KI to the reaction mixture. [31] To the best of our knowledge, prior to the present study, there had been no report on the alkylation of thiohydantoin or its derivatives with α-iodoketones that might lead to the corresponding salts. The need for the salts of heterocyclic compounds is determined by the growing interest in these compounds due to wide application in different fields of science and technology.…”
Section: Introductionmentioning
confidence: 77%
“…[35] Carrying out the reaction in acetonitrile as an easily removable solvent used in ref. [31] gave rise to a hardly separable mixture of the N-and S-ketoalkylated products, as proved by the presence of both NCH 2 and SCH 2 methylene proton signals at 4.82 and 4.05 ppm, respectively, in the 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, hydantoin A has exhibited comparable anticonvulsant activity to phenytoin [1], B showed antimycobacterial activity against Mycobacterium tuberculosis with IC 50 of 4.5 μg/mL [2], and C and D exhibited fungicidal activity with 95%–100% inhibition against Erysiphe graminis , Uromyceis appendiculatus , and Botrytis cinerea [3], E had been investigated as antitumor agent (Scheme 1). In addition, these 5-arylidene derivatives are very useful building blocks for the synthesis of various heterocycles such as 5-arylidene derivatives of imidazoline-4-one, imidazothiazine, diazinone, and diazepinone [48]. In 5-arylidene hydantoins and thiohydantoins, the arylidene carbon-carbon double bond at 5-position are as important as hydantoin or thiohydantoin moiety to the biological effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much more attention has been paid to the synthesis and evaluation of the biological activity of 5-spirotetramic and 5-spirotetronic acid derivatives. [4][5][6][7][8][9][10][11] Furthermore, novel synthetic strategies toward 2-aminoimidazolinone derivatives have been developed, [12][13][14] which have resulted in a diverse range of chemical structures and the possibility for the discovery of new lead com-pounds; various imidazolinone-containing compounds have been found in Nature or have been synthesized and reported to display a wide spectrum of biological activity. One such example is fenamidone ( Figure 1) having antimicrobial and fungicidal activities.…”
mentioning
confidence: 99%